Dietary antioxidants and health effects: what are their optimal intakes? - Vidović, Bojana (Archives of Pharmacy, 2023)
A well-balanced diet provides many compounds with antioxidant properties, such as vitamins, minerals, provitamins (β-carotene), and phytochemicals (e.g., carotenoids, polyphenols, organosulfur compounds). In addition to direct antioxidants, foods indirectly support the endogenous defense system, by providing substrates for the synthesis of glutathione, antioxidant defense enzymes, metal-binding proteins, or modulators of redox-dependent signaling pathways. Epidemiological studies indicate that higher intakes and circulating concentrations of vitamins C, E, carotenoids, and flavonoids reflect a lower risk of chronic diseases and all-cause mortality, suggesting the importance of optimal intakes of these substances. However, unlike antioxidant micronutrients, phytochemicals have no defined recommended intake levels. A diet should be based on consuming various plant foods (fruit, vegetables, legumes, whole grains, seeds, nuts), antioxidant-rich beverages, and a moderate intake of animal food products to fully exploit the health-promoting effects of dietary antioxidants.
Keywords: antioxidants; health benefits; diet; nutrients; phytochemicals